Le Notre Père dans la littérature française contemporaine - Cerbelaud, Dominique (Revue des sciences philosophiques et théologiques, 2010)
Between the end of the 19th and the end of the 20th centuries, the text of the Lord’s Prayer crops up repeatedly in contemporary French literature, either in fragmentary form or in its entirety. But it is presented in a variety of different ways: among the authors in which it appears, one finds contradictory attitudes, ranging from a respectful or explicitly religious reception of the text to attempts at parody, or even blasphemous imitation. This article examines these references, and offers a theological assessment of them.